Production of lentiviral vector with polycistronic transcripts for reprogramming of mouse fibroblast cells - Al Abbar, Akram; Nordin, Norshariza; Ngai, Siew Ching; Abdullah, Syahrilnizam (Universiti Putra Malaysia Press, 2018)
iPS cells were originally generated using monocistronic retroviral vectors carrying the Yamanaka factors 'OSKM'. The development of a polycistronic viral vector with OSKM linked by 2A peptides has simplified reprogramming procedure and reduced the risk of multiple proviral integrations and insertional mutagenesis. In this study, we demonstrated the production of the polycistronic lentiviral vector encoding OSKM in a single cassette without a reporter gene or drug-based selection system. Syncytia formations were clearly seen following the co-transfection of a lentiviral plasmid construct with the structural and packaging plasmids. The virion was collected at 48 hours post-transfection. Afterwards, the viral titers were measured by the expression of Sox2 protein from transduced HT1080 cells. Subsequently, Oct4 expression was successfully detected in mouse fibroblasts in the range of 5, 10 and 20 MOIs with expression of 90.7%, 97.5% and 98%, respectively. The results obtained from this study could be used as a model for the production of OSKM lentiviral vector for newcomers to cellular reprogramming research.